1999
DOI: 10.1109/5326.760562
|View full text |Cite
|
Sign up to set email alerts
|

A multisession comparative study of group size and group performance in an electronic meeting system environment

Abstract: Meetings are crucial elements in the functioning of organizations. Actors commonly noted as causing a meeting to lose its effectiveness (achieve the desired outcomes) are too many or too few individuals, wrong individuals, lack of goals, and hidden agenda/motives. Several researchers have focused on determining the optimal group size for a meeting. Much of this work was based on the concept that as the size of a group increases, meeting outcome measures (net value) increase until a maximum point is reached. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…First, it can be repeated in identified CMC environments to test the moderating effect of group size on cues to deception. It is anticipated that identified message exchanges increase deceivers' self-conscientiousness (Marsden & Mathiyalakan, 1999), which in turn elevates the level of arousal and causes more leakage of behavioral cues to deception. Second, it is interesting to increase the number of truth tellers in a group to explore the effect of large group sizes on cues to deception.…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it can be repeated in identified CMC environments to test the moderating effect of group size on cues to deception. It is anticipated that identified message exchanges increase deceivers' self-conscientiousness (Marsden & Mathiyalakan, 1999), which in turn elevates the level of arousal and causes more leakage of behavioral cues to deception. Second, it is interesting to increase the number of truth tellers in a group to explore the effect of large group sizes on cues to deception.…”
Section: Research Implicationsmentioning
confidence: 99%
“…As a result, deception in online groups is emerging as a severe problem. There has been extensive work in information systems and related disciplines that examines the effect of group size on various forms of group performance (Dennis, Valacich, & Nunamaker, 1990;Fjermestad & Hiltz, 1998Gallupe et al, 1992;Marsden & Mathiyalakan, 1999;Masoodian & Apperley, 1996;. It is generally reported that enlarging group size increases the amount of group output (Dennis & Wixom, 2002).…”
mentioning
confidence: 99%
“…Program attendees, however, may come to fewer sessions and thus do not receive the intended "dosage" of program content, which may diminish program effectiveness. Similarly, there are theoretical and empirical reasons to believe that group size, for example, may be an important determinant of participant learning and behavior change (Marsden & Mathayalakan, 1999); effects on program outcomes of variability in this and many other contextual variables remain unexplored.…”
mentioning
confidence: 98%
“…RELATION WORK In our paper [4], the relation works were introduced. Such as, Kirda et al [5] provided a service architecture for mobile teamwork, Caporuscio and Inverard provided [6] another framework for supporting mobile and collaborative work, Sacramento et al [7] gave a middleware for developing collaborative applications for mobile users, Patwardhan et al [8], Sendonaris et al [9,10] gave a system description, implementation aspects and performance analysis for user cooperation; JR Marsden et al [11] discussed a multi-session comparative study of group size and group performance in an electronic meeting system environment and so on..…”
Section: Introductionmentioning
confidence: 99%